RECQ helicases are deregulated in hematological malignancies in association with a prognostic value. Issue 1 (December 2016) - Viziteu, Elena; Kassambara, Alboukadel; Pasero, Philippe; Klein, Bernard; Moreaux, Jerome
Abstract Background RECQ helicase family members act as guardians of the genome to assure proper DNA metabolism in response to genotoxic stress. Hematological malignancies are characterized by genomic instability that is possibly related to underlying defects in DNA repair of genomic stability maintenance. Methods We have investigated the expression ofRECQ helicases in different hematological malignancies and in their normal counterparts using publicly available gene expression data. Furthermore, we explored whetherRECQ helicases expression could be associated with tumor progression and prognosis. Results Expression of at least oneRECQ helicase family member was found significantly deregulated in all hematological malignancies investigated when compared to their normal counterparts. In addition, RECQ helicase expression was associated with a prognostic value in acute myeloid leukemia, chronic lymphocytic leukemia, lymphoma and multiple myeloma. Conclusion RECQ helicase expression is deregulated in hematological malignancies compared to their normal counterparts in association with a prognostic value. Deregulation of RECQ helicases appears to play a role in tumorigenesis and represent potent therapeutic targets for synthetic lethal approaches in hematological malignancies.